The Spm (En) transposable element controls the excision of a 2-kb DNA insert at the wx(m-8) allele of Zea mays - Schwarz-Sommer, Zs. (1984)
The waxy (Wx) locus of Zea mays was cloned from strains carrying the wild-type and wx(m-8) mutant alleles. The receptor component of the Suppressor-Mutator (Spm) controlling element system in the wx(m-8) allele was shown to be a 2 kb long insertion within the transcribed region of the Wx gene. The insertion, termed Spm-I8, is excised during somatic reversion events induced by the autonomous controlling element Enhancer (En), which is an equivalent to Spm. Integration of Spm-I8 into the Wx gene generates a 3-bp target site duplication. Spm-I8 has a 13 bp long inverted repeat at its termini. The ends of the element can be further folded to build a large double-stranded structure consisting of five perfectly matching double-stranded regions of 9–13 bp in length, interrupted by single-stranded loops. A comparison of the wild-type and wx(m-8) alleles revealed two additional insertions 6 (insert-1) and 0.25 (insert-2) kb in length. No En-induced excision of insert-1 and insert-2 could be detected so far. There is remarkable structure and sequence homology between Spm-I8 and the transposable elements Tam1 and Tam2 of Antirrhinum majus at their termini, reflecting a possible evolutionary and/or functional relationship between transposons in different plant species.